Performance during frequency certainty and frequency uncertainty conditions in normal-hearing and hearing-impaired human subjects / Wan Nur Asyiqin Rasidi - Wan Nur Asyiqin, Rasidi (2017)
The detection of sound is enhanced when the frequency of the sound is known (frequency certainty) as compared 10 when the frequency is not known (frequency uncertainty). The present study investigated the performance of normal-hearing and mild-to-moderate sensorineural hearing loss (SNHL) subjects in frequency certainty and frequency uncertainty conditions. Frequency ce1tainty was induced by presenting preceding cue tones that matched the frequency of the to-be-detected signals, while frequency uncertainty involved the detection of randomly selected uncued tonal signals from a set of five different frequencies presented in background noise in a two-interval forced choice (2IFC) task. Results from the current study showed that performance in the frequency certainty in normal-hearing subjects were better compared to their performance in frequency uncertainty condition. The uncertainty effect (difference in detection rates in frequency uncertainty and uncertainty) was estimated to be between 2.7 to 3.7 dB throughout all centre frequencies (0.57, I, 2. 15 and 4 kHz). However, in S HL subjects, the uncertainty effect was significantly lower ( 1.5 dB) than their age- and sex-matched controls (3.7 dB). In addition, the change in the uncertainty effect in all the subject showed significant negative correlation with a measure of cochlear frequency selectivity known as critical ratio (CR). It is suggested that the loss of uncertainty effect in SNHL subjects could have an adverse effect on their ability to detect speech signals in noise.